Mathematical modeling of changes in groundwater level in repeated cropping lands: Mathematical modeling of changes in groundwater level in repeated cropping lands - Murodullaev, Bakhtiyor; Haknazarova , Dilobar (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Abstract: The issue of creating and solving a numerical model of the filtration process of groundwater interacting with surface water in lands with repeated crops is considered in the article. Conducting research on this process using mathematical modeling and solving it, is an urgent problem. Before presenting the solution to this problem, mathematical and numerical modeling were sufficiently studied and analyzed in scientific literature. In the studies of aquifers, the values of the underground and water level indicators were obtained in relation to the lower horizontal impermeable layer, and the mathematical model of groundwater flow in the aquifers was described by a special derivative of the parabolic-type nonlinear differential equation. Computational experiments have shown that irrigation water is the main factor that has a significant impact on the groundwater level